Liquid-Liquid Extraction of Platinum from Chloride Media by N,N'-Dimethyl-N,N'-Dicyclohexyltetradecylmalonamide - Costa, M. Clara (2013)
Liquid-liquid extraction of platinum(IV) from chloride media was carried out using N,N'-dimethyl-N,N'-dicyclohexyltetradecylmalonamide (DMDCHTDMA) in 1,2-dichloroethane. Platinum can be effectively extracted by DMDCHTDMA without addition of tin(II) chloride, since extraction percentages (%E) of 88% and 99% have been achieved from 6 M and 8 M HCl, respectively. Moreover, platinum can be successfully stripped through a simple contact with a 1 M HCl solution. The effect of some experimental parameters such as equilibration time, diluent, extractant and HCl concentrations was systematically investigated. The loading capacity of DMDCHTDMA was also evaluated. Data obtained from successive extraction-stripping cycles suggest a good stability pattern of DMDCHTDMA. Preliminary extraction data achieved with single metal ion solutions pointed out to a possible separation of platinum(IV) from palladium(II).